2013
DOI: 10.1371/journal.pone.0068926
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Pulsed Ultrasound Accelerates Tooth Movement via Activation of the BMP-2 Signaling Pathway

Abstract: The present study was designed to determine the underlying mechanism of low-intensity pulsed ultrasound (LIPUS) induced alveolar bone remodeling and the role of BMP-2 expression in a rat orthodontic tooth movement model. Orthodontic appliances were placed between the homonymy upper first molars and the upper central incisors in rats under general anesthesia, followed by daily 20-min LIPUS or sham LIPUS treatment beginning at day 0. Tooth movement distances and molecular changes were evaluated at each observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
56
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 51 publications
(56 reference statements)
8
56
1
10
Order By: Relevance
“…In the other hand, osteoblasts seem to respond differently from cementoblasts after LIPUS application, as previously reported (ElBialy et al, 2011;Xue et al, 2013;Al-Daghreer et al, 2014). In the in vivo experiment performed by Inubushi et al (2013), osteoclasts located along the bone surface were otherwise increased after LIPUS application in one of the experimental groups.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In the other hand, osteoblasts seem to respond differently from cementoblasts after LIPUS application, as previously reported (ElBialy et al, 2011;Xue et al, 2013;Al-Daghreer et al, 2014). In the in vivo experiment performed by Inubushi et al (2013), osteoclasts located along the bone surface were otherwise increased after LIPUS application in one of the experimental groups.…”
Section: Discussionsupporting
confidence: 74%
“…Histological findings demonstrated increased alveolar bone remodeling due to the elevated number of osteoclast (OC) cells along the bone surfaces of the moved teeth that were subjected to ultrasound application (ElBialy et al, 2011;Inubushi et al, 2013;Xue et al, 2013;Al-Daghreer et al, 2014). The LIPUS-driven increase in the OC number might be attributed to the stimulation of their differentiation as a result of an upregulation of the RANK-L gene expression in osteoblasts (Inubushi et al, 2013;Xue et al, 2013), which generates the most important mediator for osteoclastogenesis (Titorencu, Pruna, Jinga, & Simionescu, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…2 Fávaro-Pípi et al found that LIPUS stimulation in rats significantly increased BMP-4 expression on days 7 and 25. 9 10,23 In this study using MHCs extracted from human mandibular fracture sites, only BMP-4 expression was increased in the absence of LIPUS application on days 4 and 8 (Fig. 1).…”
Section: Discussionmentioning
confidence: 62%
“…The present study shows an increase in the expression of Cbfa1/Runx2 and Cox-2 mRNA at an early stage, supporting the previous studies. It was previously reported that LIPUS increased orthodontic tooth movement distance and the BMP-2 signaling pathway in a rat model 17) . 16) .…”
Section: Discussionmentioning
confidence: 84%